Making as a tool of self-examination and search for meaning : sifting through remaining residue as the tide of faith ebbs away : an exegesis presented with exhibition as fulfilment of the requirements for thesis Master of Fine Arts at Massey University, Wellington, New Zealand - McGrath, Shane Michael (Massey University, 2010)
At the commencement of this thesis I saw myself standing at the outer limits of my knowledge with my nose pressed against a wall of demarcation. This wall was built from my willingness to tolerate systems of control in silence and from my unwillingness to make my beliefs and personal convictions known. I set out at the start of this journey with two intentions. I want to raise my voice because I didn’t want to pretend about my faith anymore. And for the first time use my art practice as a mouthpiece to tell these truths.
Keywords: Religion and art; Catholic faith; Personal belief and art; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies::410202 Fine arts studies (incl. sculpture and painting)